THE MEDIATING ROLE OF CONTEXTUAL AMBIDEXTERITY IN THE RELATIONSHIP BETWEEN DIGITAL TRANSFORMATION, INNOVATION CAPABILITY, AND SME PERFORMANCE - Gilbert Johan Martin Sinaga (PT Akselerasi Karya Mandiri, 2026)
This study addresses a critical gap in SME research, where prior studies emphasize the direct effects of digital transformation (DT) and innovation capability (IC) on performance while overlooking the underlying organizational mechanisms. This study examines how SMEs convert DT and IC into performance through contextual ambidexterity (CA) in a developing economy. Using data from 350 SMEs in Indonesia and PLS-SEM analysis, the results show that DT (β = 0.270, p < 0.01) and IC (β = 0.170, p < 0.05) significantly improve performance, with DT having a stronger effect. CA also enhances performance (β = 0.260, p < 0.01) and mediates the effects of DT (β = 0.092, p < 0.01) and IC (β = 0.052, p < 0.05). These findings indicate that the performance impact of DT and IC depends on firms’ ability to balance exploration and exploitation. This study contributes by offering a mechanism-based explanation that integrates DT and IC and positions contextual ambidexterity as a key driver of SME performance in emerging economies.